Border Crossings in Maríe Redonnet's Splendid [Seaside] Hôtel - Elizabeth A. Mazza-Anthony (Studies in 20th & 21st Century Literature, 1996)
Maríe Redonnet crosses previously established boundaries in Splendid Hôtel and Seaside. Her writing flows across traditional literary genres as she revisits certain motifs, characters, and situations in her novel and play. In addition to crossing the border between the novel and theater, she echoes the works of other authors—specifically Rimbaud and Duras. Moreover, within a particular text Redonnet erases subject boundaries. That is to say, her characters are not individuals; their uniqueness is washed away by a continual ebb and flow of common characteristics and traits. By creating such fluid personae, Redonnet captures the societal homogeneity that is symptomatic of "surmodernity" as defined by Mark Augé: "the acceleration and overabundance of events and space and the individualization of references [are] the three elements of excess with which we have tried to characterize the supermodern condition." As she weaves her "literary" text and intertext she also incorporates elements from other disciplines. Indeed, her references to the cinema as well as to the family photograph obscure conventional distinctions between "high" and "mass" culture. At the same time, Redonnet's blurred boundaries create a sense of longing for the past, or more precisely, for past representations. This element of nostalgia sends the characters and, at times, the reader/spectator into the familiar. Thus, traces of past representations emerge in Redonnet's writing as in a palimpsest. In conclusion, by crossing previously established borders, Maríe Redonnet paints the permeable "supermodern" boundaries among individuals, text/intertext, and photography/film/literature.
Keywords: Maríe Redonnet; boundaries; Splendid Hôtel; Seaside; traditional literary genres; genre; motifs; characters; situation; novel; theater; play; Rimbaud; Duras; subject boundaries; individuals; common characteristics; traits; fluid personae; societal homogeneity; homogeneity; surmodernity; Mark Augé; literary; cinema; family photograph; high culture; mass culture; nostalgia; element; reader; spectator; familiar; palimpsest; supermodern; text; intertext; photography; film; literature